The management steps towards the success and sustainability of Mae Kampong tourism community - Jitpakdee, Pit; Harun, Azhar; Mohd. Zain, Zawiyah (2016)
suburban areas of Thailand. For a couple of decades, the CBT has been linked to the development goals in terms of increasing income for local people, improving their life quality, and leading them out of poverty.Not only CBT communities that gained advantages from this kind of tourism, but tourists benefit from it by experiencing the local way of life as well. However, the CBT is not as simple as just thinking and doing.The communities need to clearly understand how to manage and operate the CBT sustainably.Otherwise it would be just a firework that popped in the sky and vanished.So, the management of the CBT community is the key to success and sustainability.This paper analyzes the management steps, and extracts the management know-how that led them to the success of a community that is located in the mountainous area of Chiang Mai which is in the Northern region of Thailand namely Mae Kampong village.By collecting data through observation and interviews, and also reviewing related literatures, it is believed that the success and sustainability of Mae Kampong’s CBT operation is based upon the continuous process of the management cycle.